If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying N + 2n = 30 Solving N + 2n = 30 Solving for variable 'N'. Move all terms containing N to the left, all other terms to the right. Add '-2n' to each side of the equation. N + 2n + -2n = 30 + -2n Combine like terms: 2n + -2n = 0 N + 0 = 30 + -2n N = 30 + -2n Simplifying N = 30 + -2n
| 6x+4x=74 | | 4.0=8.4/X | | 6(a-6)=48 | | a^3x-9ax^3=0 | | (p-6)(p-7)=0 | | 3x+2x=5+3 | | 3(d-4)=15 | | 8=4c-4 | | 4x+7,x=6 | | 6r+6=21r+9 | | y=2140x-53500 | | 47=11+12W | | 3/4+10=190 | | 8y+5x-3y+7-2x= | | 2x-5=4x-1+5 | | log[9]x=log[9]5+log[9]6-log[9]3 | | -5(1+2w)=20 | | 4x-16+6=2x+-6+2x | | 2-4x=-62 | | 1/2x-5+2x+2=10 | | -5(-1+k)=25 | | 7x+21=x/7 | | (d+1)=64 | | 3y+6y+8y= | | 2/3*2*-8= | | -4x+9x=-50 | | x^3+15x^2+72x+108=0 | | 4y-10=6+y | | 2x^2+25x+48=0 | | 3/8*2/3 | | 4/3+2=14/3 | | 2/5(f+6)-f |